2014
DOI: 10.4102/rw.v5i1.41
|View full text |Cite
|
Sign up to set email alerts
|

Integration of sources in academic writing: A corpus-based study of citation practices in essay writing in two departments at the University of Botswana

Abstract: The ability to cite sources appropriately is an important feature of academic writing. Academic writers are expected to integrate ideas of others into their texts and take a stance towards the reported material as they develop their arguments. Despite this importance, research has shown that citation presents considerable difficulties for students, particularly non-native English speakers. Such difficulties include using citations effectively in writing and understanding them in reading, expressing one’s voice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
2
13
0
1
Order By: Relevance
“…Akademik metnin bu önemli özelliğini yazarlar, araştırmacının araştırma alanını, araştırmalarının önem ve bağlantılılarını, araştırma alanındaki yetkinliklerinin gösterilmesi, yönteminin ve izleklerin yeterliliği ve doğruluğunun sergilenmesi, çeşitli yöntem ve izleklerin kanıtlanması, bulguları meşrulaştırma, iddialarının meşruiyeti ve okuyucuları yeni iddiaları kabul etmeye ikna etme gibi çok çeşitli anlatı-bilimsel amaçlar için kullanırlar (Mansourizadeh ve Ahmad, 2011). Ancak, araştırmalar, ana dili İngilizce olmayan yazarların atıf yapma konusunda önemli zorluklar yaşadıklarını göstermiştir (Davis, 2013;Ramoroka, 2014).…”
Section: Discussionunclassified
“…Akademik metnin bu önemli özelliğini yazarlar, araştırmacının araştırma alanını, araştırmalarının önem ve bağlantılılarını, araştırma alanındaki yetkinliklerinin gösterilmesi, yönteminin ve izleklerin yeterliliği ve doğruluğunun sergilenmesi, çeşitli yöntem ve izleklerin kanıtlanması, bulguları meşrulaştırma, iddialarının meşruiyeti ve okuyucuları yeni iddiaları kabul etmeye ikna etme gibi çok çeşitli anlatı-bilimsel amaçlar için kullanırlar (Mansourizadeh ve Ahmad, 2011). Ancak, araştırmalar, ana dili İngilizce olmayan yazarların atıf yapma konusunda önemli zorluklar yaşadıklarını göstermiştir (Davis, 2013;Ramoroka, 2014).…”
Section: Discussionunclassified
“…In citing other author's work, one of the most important aspects to consider is the use of appropriate RVs; this is because writers must match the choice of RVs with their position or stance toward the information cited in the reference (Ramoroka, 2014). In other words, the choice of RVs will enable writers to position their work in connection with the works of other writers in a particular field of research (Yeganeh & Boghayeri, 2015)this study investigated the frequency of the most used reporting verbs and their function in the Introduction and Literature Review sections of research articles (RAs.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the choice of RVs will enable writers to position their work in connection with the works of other writers in a particular field of research (Yeganeh & Boghayeri, 2015)this study investigated the frequency of the most used reporting verbs and their function in the Introduction and Literature Review sections of research articles (RAs. Hyland (2002) claims that RVs are used to express the author's point of view and connect it to the reader's ideas but writers in a particular discipline or language may use RVs differently from writers in other disciplines or languages do (Hyland, 1999;Ramoroka, 2014). Similarly, according to Thomas & Hawes (1994), RVs are used to imply the author's belief or opinion and to show his or her position towards other author's works.…”
Section: Introductionmentioning
confidence: 99%
“…Although RVs are one of the essential items in writing statements for academic writing (Hyland, 1998), the findings from the research performed on students' academic writing (Ramoroka, 2014) and Master's theses in particular Noor, 2014, 2015;Pramoolsook, 2015, 2016) show that students are not always fully aware of how to use RVs appropriately. Besides the semantic evaluation of the RVs, the paper's focus was also on the syntactic aspects of the structures containing the RVs, i.e.…”
Section: Electronic Issnmentioning
confidence: 99%
“…Similarly, Liardét and Black (2019) have found that L2 learners majoring in predominantly soft domain disciplines rely on merely acknowledging structures such as state or according to in their university assignments, providing thus no subjective stance on the reported source. Analysing a corpus of 80,000 words from essays written by non-native undergraduates of two university departments of media studies and education, Ramoroka (2014) concludes that soft domain students use informative RVs neutral in passing the information from the source to the reader rather than interpreting the information cited. Similar results emphasising students' negligence to employ RVs in their variety were obtained by Manan and Noor (2015), who examined the use of RVs in undergraduate Master's theses by L2 learners majoring in English studies.…”
Section: Genre Studies On Reporting Verbs Across Disciplinesmentioning
confidence: 99%